Peran Serta Masyarakat dalam Melestarikan Budaya Lokal sebagai Identitas Bangsa untuk Menjaga Keutuhan NKRI - Zainudin Hasan; Ahmad Farhan NP; Alvarian L Tobing; Hazbullah Indra Rajasa; Ramadhan Fariz Nugraha; Wahyu Ramadhan Herpa (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2024)
Bhinneka Tunggal Ika is very inherent for us Indonesian citizens. Bhinneka Tunggal Ika is a defense of harmony between each tribe, respecting differences while also strengthening Indonesia's identity profile which has existed for a long time. The development of the globalization era can bring more modern changes to people's lifestyles, especially in Indonesia. The development of the era of globalization itself makes people tend to choose new cultures that are considered simpler than the local culture in Indonesia. Preserving Indonesian culture and customs is an important aspect in the lives of indigenous peoples, because indigenous peoples are still synonymous with a lifestyle based on local customs. Therefore, this article aims to explain efforts to preserve Indonesian culture in the era of globalization. The method used in this research is qualitative with the data collection technique being library research, where the author examines several library sources as references in this writing. The results of this research show that it is very important to preserve Indonesian culture and traditional communities. In current developments, information has become very influential on human thinking patterns. To overcome this, there needs to be awareness, especially among the younger generation, of the importance of local culture as national identity and being able to preserve and maintain local culture. Efforts to preserve and preserve Indonesian culture are carried out in two ways. That is; cultural experience and cultural knowledge.